(untitled) (Mazahib, 2026)
This study investigates how international institutions, particularly United Nations bodies, engage in terminological engineering that reshapes global moral and legal discourse. It argues that terms related to gender, sexuality, and human identity are not linguistically neutral but serve as instruments of Western ideological hegemony. Through the analysis of international instruments such as CEDAW, the Beijing Platform for Action, and the Yogyakarta Principles, the paper demonstrates how linguistic normalization embeds secular-liberal assumptions within international law. Drawing upon the Islamic intellectual tradition, especially the concepts of fiá¹rah (innate disposition) and iá¹£á¹ilÄá¸¥ (ethical terminology), the study contrasts secular and sacred epistemologies of law and language. It concludes that the global diffusion of these terminologies constitutes not merely a legal process but an epistemological transformation that redefines human ontology, undermines ethical pluralism, and challenges the moral sovereignty of Islamic jurisprudence.